Analysis, Design, And Experimentation of a Buck Converter Based on the Three-state Switching Cell Operating in Overlapping Mode - de Seixas, Falcondes José Mendes; Balestero, Juan Paulo Robles; de Seixas, Claudiner Mendes; Tofoli, Fernando Lessa; Torrico-Bascopé, Grover Victor (Eletrônica de Potência, 2013)
This work presents the detailed analysis of the dc-dc nonisolated buck converter based on the three-state switching cell operating in overlapping mode, which occurs when the duty cycle of the active switches is higher than 0.5. Only part of the load power is processed by the active switches due to the use of the autotransformer, thus reducing the peak current through the switches to half of the load current, as higher power levels can then be achieved by the proposed topology. The volume of reactive elements i.e. inductors and capacitors is also decreased since the ripple frequency of the output voltage is twice the switching frequency. Due to the intrinsic characteristics of the topology, total losses are distributed among all semiconductors. Another advantage of this converter is the reduced region for discontinuous conduction mode when compared to the conventional buck converter as demonstrated by the static gain plot. Besides, the input current is continuous and the ripple current is reduced, what is not verified in the classical buck converter. The theoretical approach is detailed through qualitative and quantitative analyses, design procedure, and a comparison with similar topologies. Finally, an experimental prototype rated at 1 kW is implemented, while the main experimental results are presented and adequately discussed to clearly identify its claimed advantages.